Crowdfunding Sharia Financing Model as Alternative Business Capital Financing for MSMES - Andri Ibrahim, Mohamad; Eprianti, Nanik; Rizki Febriadi, Sandy (KnE Social Sciences, 2023)
In the era of the Industrial Revolution 4.0, there are currently financial product innovations, one of which is fintech (financial technology). Crowdfunding is a fintech product with a Sharia concept, that can be accessed on the internet network. Likewise, it is a form of funding for those who need funds for business development. In the Shariah concept, crowdfunding is a form of work or syirkah where there is a collective effort from several people who come together to finance a business through a digital platform called financial technology. This is a qualitative research, using bibliometric analysis approach. Crowdfunding aims to be an alternative financing, in Indonesia itself. Sharia Fintech had emerged in 2017, the Indonesian Sharia Fintech Association (AFSI) has been formed by the Tazkia Fintech Study Center with members of 8 Sharia fintech companies, the latest data shows that in 2020 the addition of the number of AFSI members consists of 18 members of peer to peer (p2P) lending, 27 members of digital financial innovation (IKD), four members of Sharia equity crowdfunding (ECF), 2 payment members, 2 non-fintech members, and 9 sharia members, and financial partner. Keywords: crowdfunding, MSMEs, bibliometric analysis